Pengaruh Tipe Kepemimpinan Transformasional dan Transaksional Kepala Ruangan terhadap Komitmen Organisasional Perawat di RSI UNISMA Malang - Azzuhri, Misbahuddin; Herawati (Universitas Brawijaya, Indonesia, 2014)
The aim of this study is to know the effect of head nurse's type of transformational and transactional leadership towards nurse'organizational commitment at RSI UNISMA MALANG. The research method used descriptive analysis with cross sectional approach on ninety respondents. We have conducted the descriptive statistic test, double linear regression analysis, testing hypothesis, dominant variable test. Type of transformational and transactional leadership of head nurse gave significant affect simultaneously and partially to the nurse'organizational commitment in Islamic Hospital UNISMA Malang. Transformational leadership type of head nurse affects dominantly to the nurse'organizational commitment in Islamic Hospital Malang.